The impact of metabolic reprogramming in hepatocellular carcinoma on T cell - Liao, Dong-Xu; An, Xiang; Huang, Gui-Xiang; Yuan, Tong-Ling (Frontiers in Immunology, 2025)
Hepatocellular carcinoma (HCC) is the predominant type of liver cancer, characterized by high incidence and mortality rates. Despite advancements in surgical and systemic therapies, the prognosis remains poor due to the asymptomatic nature of early-stage HCC. Metabolic reprogramming in HCC cells usually creates an immunosuppressive tumor microenvironment (TME), thereby impeding T cell-mediated antitumor immunity. This review focuses on the metabolic reprogramming patterns in HCC, their impact on T cell function, and the potential of metabolic-immune targeted combination therapies. We emphasize that nutrient competition and the accumulation of inhibitory metabolites are key mechanisms underlying T cell suppression in the TME. This review provides an update on the complex metabolic-immune interactions and helps to identify new therapeutic targets to improve the efficacy of immunotherapy for HCC.